Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1177/00031348211038555
|View full text |Cite
|
Sign up to set email alerts
|

The Virtual Interview Experience for MATCH 2021: A Pilot Survey of General Surgery Residency Program Directors

Abstract: Background Virtual interviews (VIs) for the 2020 residency application season were mandated as a result of the COVID-19 pandemic. We aimed to determine the perspectives of general surgery (GS) program directors (PDs) on the benefits and drawbacks of VIs. Methods A 14-item survey was emailed to all GS PDs from programs identified on the American Council for Graduate Medical Education website. Program directors were asked about the cost-time benefit of VIs, its ability to assess candidates, and their thoughts on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Thus, so far, most evidence supports that faculty members and program directors have shown good satisfaction with virtual interviews but are still not fully confident of replacing face-to-face interviews with virtual interviews in the future. One study explored the lack of trust in virtual interviews; it showed that 50% of PD suggested that virtual interviews made the selection committee rely much more on the applicant’s objective data rather than the interview itself; 75% and 67%, respectively, disagreed or strongly disagreed that E-interviews allowed easier assessment of the applicant’s fit, personality, and communication skills [ 26 ]. In contrast, our study was highly encouraging from the faculty point of view, as 65.4% of the faculty members agreed or strongly agreed that virtual interviews allowed them to form an impression about the applicants’ personality, while 17.9% were neutral, and 16.8% were unsatisfied.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, so far, most evidence supports that faculty members and program directors have shown good satisfaction with virtual interviews but are still not fully confident of replacing face-to-face interviews with virtual interviews in the future. One study explored the lack of trust in virtual interviews; it showed that 50% of PD suggested that virtual interviews made the selection committee rely much more on the applicant’s objective data rather than the interview itself; 75% and 67%, respectively, disagreed or strongly disagreed that E-interviews allowed easier assessment of the applicant’s fit, personality, and communication skills [ 26 ]. In contrast, our study was highly encouraging from the faculty point of view, as 65.4% of the faculty members agreed or strongly agreed that virtual interviews allowed them to form an impression about the applicants’ personality, while 17.9% were neutral, and 16.8% were unsatisfied.…”
Section: Discussionmentioning
confidence: 99%
“…Future internal medicine recruitment will be shaped by the experiences of the 2020-2021 recruitment season. Like some other specialties, 28 , 29 , 30 , 31 , 32 , 33 many internal medicine program directors plan to incorporate virtual interviews into future recruitment cycles. This shift suggests that a hybrid approach may become the norm even after the COVID-19 pandemic ends.…”
Section: Discussionmentioning
confidence: 99%
“…37 Not all applicants and program directors felt that virtual interviews alone were sufficient in providing accurate representation of a candidate or the program culture. 1,38,39 Some program directors believed that virtual interviews decreased their ability to assess a candidate's fit, particularly regarding interpersonal communication skills, clinical skills, and genuine interest in the program. 7,16,24 Some applicants expressed that having informal interactions with other residents and faculty, as well as opportunities for program tours, were important components in their assessments of the program's culture and structure.…”
Section: Challenges and Mitigation Strategiesmentioning
confidence: 99%